International law and history : modern interfaces / Ignacio de la Rasilla. - Rasilla, Ignacio de la (Cambridge studies in international and comparative law, 2021)
This interdisciplinary exploration of the modern historiography of international law invites a diverse assessment of the indissoluble unity of the old and the new in the most global of all legal disciplines. The study of the history of international law does not only serve a better understanding of how international law has evolved to become what it is and what it is not. Its histories, which rethink the past in the present, also influence our perception of contemporary matters in international law and our understandings of how they may potentially unfold. This multi-perspectival enquiry into the dominant modes of international legal history and its fundamental debates may also help students of both international law and history to identify the historical approaches that best suit their international legal-historical perspectives and best address their historical and legal research questions.